School of Economic French - I. S. Franceva (Vestnik MGIMO-Universiteta)
Economic French at MGIMO-University is based on the teaching methods developed by talented Methodist practitioner assistant professor L.L. Potushanskoy. She and her colleagues G.M. Kotova, N. Kolesnikova, I.A. Yudina created well-known in our country methodical complex of three textbooks. This complex is built on clear guidelines to facilitate the natural development of language skills "from simple to complex" and represents the effective approach to language learning: Currently, the department is constantly expanding its boundaries of school teaching economic and business of the French language in accordance with the emerging new special courses on the economics faculties.